Structure and Stability of Gas Adsorption Complexes in Periodic Porous Solids as Studied by VTIR Spectroscopy: An Overview - Montserrat R. Delgado (Applied Sciences, 2020)
Variable-temperature infrared (VTIR) spectroscopy is an instrumental technique that enables structural characterization of gas-solid adsorption complexes by analysis of meaningful vibrational modes, and simultaneous determination of the standard enthalpy change (DH0) involved in the gas adsorption process, which allows one to quantify the stability of the corresponding complex. This is achieved by a van’t Hoff analysis of a set of IR spectra recorded over a sufficiently large temperature range. Herein, the use of this versatile spectroscopic technique is demonstrated by reviewing its application to the study of carbon monoxide, carbon dioxide and dinitrogen adsorption on several (alkaline) zeolites, which can be regarded as the archetype of periodic porous solids.